Interaction of light with hematite hierarchical structures: Experiments and simulations - Distaso, Monica; Zhuromskyy, Oleksandr; Seemann, Benjamin; Pflug, Lukas; Mackovic, Mirza; Encina, Ezequiel Roberto; Klupp Taylor, Robin; Müller, Rolf; Leugering, Günter; Spiecker, Erdmann; Peschel, Ulf; Peukert, Wolfgang (Journal of Quantitative Spectroscopy & Radiative Transfer, 2017)
Mesocrystalline particles have been recognized as a class of multifunctional materials with potential applications in different fields. However, the internal organization of nanocomposite mesocrystals and its influence on the final properties have not yet been investigated. In this paper, a novel strategy based on electrodynamic simulations is developed to shed light on how the internal structure of mesocrystals influences their optical properties. In a first instance, a unified design protocol is reported for the fabrication of hematite/PVP particles with different morphologies such as pseudo-cubes, rods-like and apple-like structures and controlled particle size distributions. The optical properties of hematite/PVP mesocrystals are effectively simulated by taking their aggregate and nanocomposite structure into consideration. The superposition T-Matrix approach accounts for the aggregate nature of mesocrystalline particles and validate the effective medium approximation used in the framework of the Mie theory and electromagnetic simulation such as Finite Element Method. The approach described in our paper provides the framework to understand and predict the optical properties of mesocrystals and more general, of hierarchical nanostructured particles.
Keywords: Effective medium approximation; FEM; Maxwell-Garnett theory; Mesocrystals; Scattering; T-Matrix

Synthesis of Goethite α-FeOOH Particles by Air Oxidation of Ferrous Hydroxide Fe(OH)2 Suspensions: Insight on the Formation Mechanism - Klupp Taylor, Robin; Encina, Ezequiel Roberto; Distaso, Monica; Taylor, Robin N. Klupp; Peukert, Wolfgang (Crystal Growth & Design, 2015)
Iron oxide and iron oxyhydroxide particles, particularly, the goethite extgreeka-FeOOH phase, are environmentally friendly materials and are used in various technological applications as adsorbents, precursors of Fe powders for magnetic recording media, and pigments. In this work, the formation process of extgreeka-FeOOH by air oxidation of Fe(OH)2 suspensions has been studied. The effects of the air flow rate, as well as of the reactant concentration ratio, R (=[(OH)-]/[Fe(II)]), on the reaction product were analyzed. It has been found that the morphology and the size of the extgreeka-FeOOH particles can be modified by means of the air flow rate. Furthermore, by performing a detailed microscopic analysis of the morphology of the initial, intermediate, and final reaction products, we have obtained evidence of epitaxial growth of extgreeka-FeOOH on the Fe(OH)2 substrate. It is suggested that the similarity between the anion arrangements in both phases facilitates this process. Based on these results, a pathway for the formation of extgreeka-FeOOH in highly alkaline medium is proposed in which the size and shape of the initial Fe(OH)2 particles plays a significant role in the formation the extgreeka-FeOOH particles obtained upon completion of the oxidation process.
EAM Import::2019-03-12
Keywords: Oxidation reactions; Atmospheric chemistry; Suspensions; Anions; Oxidation